Zinc Oxide-Catalysed Photo-Oxidative Degradation of Chlorophenols - Gaya, Umar Ibrahim (2009)
Chlorophenols are priority pollutants that must be eradicated from the environment owing to the severity of their toxicity and resistance to traditional treatment. Photocatalytic oxidation is an advanced oxidation method which has proven reliability to eliminate persistent pollutants from air and water. The activity of zinc oxide for pollutant removal by photocatalytic oxidation has been well established. In this work the photocatalytic transformation of 4-chlorophenol, 2,4-dichlorophenol and 2,4,6-trichlorophenol in irradiated ZnO suspensions at 299 K was studied. The effect of operating parameters such as catalyst and concentration doses on the decomposition rate of these para-chlorinated compounds has been investigated and optimised. It was discovered that the optimum feed concentration for the phenolic compounds is 50 mg L-1. The optimum amount of ZnO was determined for the degradation of 4-chlorophenol, 2,4-dichlorophenol and 2,4,6-trichlorophenol which decreased as with increasing of chlorine substituent. For 4-chlorophenol degradation the first clearer description of the effect of doses using response surface was reported. Kinetic profiles on the decomposition of chlorophenols over ZnO were consistent with pseudo-zeroeth order rate scheme. For 2,4-dichlorophenol and 2,4,6- trichlorophenol the decomposition was slow at the short irradiation time. It was found that the degradability of chlorophenols increased as the number of ringchlorine increased. The effect of pH on the destruction rate was found to be influenced by chlorophenol adsorption and dissociation equilibrium. The effect of different anions on the rate of chlorophenol degradation was evaluated by utilising sodium salts as additives. Except for 4-chlorophenol it was found that, inorganic anion additives such as SO4 2-, S2O8 2- and Cl- demonstrated inhibition to the decomposition rate of chlorophenol. HPO4 2- was found to show strongest inhibition and could even hamper the degradation of 4-chlorophenol. The progression of intermediates during the mineralisation of chlorophenols was chromatographed on high performance liquid chromatograph (HPLC). The structure elucidation of pathway products en route to mineralisation of chlorophenols was performed by the combined gas chromatography-mass spectrometry (GC-MS) and HPLC methods. The study disclosed some hitherto unreported intermediates of photocatalytic decomposition of 4-chlorophenol and 2,4-dichlorophenol. Catechol was detected as new intermediate of 4-chlorophenol degradation. Similarly, 4- hydroxybenzaldehyde, benzoquinone and 4-chlorophenol are for the first time reported for 2,4-dichlorophenol degradation. The work also revealed the intermediates of 2,4,6-trichlorophenol which have not been in literature. It is highlighted herein the mechanism of formation of all pathway intermediates.